2020
DOI: 10.4314/jasem.v24i5.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Crude Oil Degradation by <i>Monocillium sp.</i> and <i>Aspergillus niger</i>

Abstract: Fungi dwelling in soils contaminated by petroleum products can survive on these hydrocarbons due to the highly effective extracellular enzymes. Species belonging to the genus, Aspergillus are known to be efficient degraders of various classes of hydrocarbons as well as other organic contaminants. In this study, the biodegradation of crude oil by Aspergillus niger and Monocillium sp. were compared using laboratory microcosms.The moulds were isolated from a site receiving effluent from a petroleum refinery. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…AI-Jawhari (2014) in a related study on single and mixed culture of fungi reported similar findings; but it contradicts the findings of Nagarajan and Loh (2015), Nwankwegu et al (2016) and Praveen et al (2016), in which the degradation rate was observed to be greater in the consortium than the individual fungi. A similar study by Odili et al (2020), it was observed that Aspergillus niger and Monocillium sp. degradaed crude oil better when they were used individually than in consortium.…”
Section: Biodegradation Of Btex By Gliocladium Sp and Aspergillus Tesupporting
confidence: 68%
“…AI-Jawhari (2014) in a related study on single and mixed culture of fungi reported similar findings; but it contradicts the findings of Nagarajan and Loh (2015), Nwankwegu et al (2016) and Praveen et al (2016), in which the degradation rate was observed to be greater in the consortium than the individual fungi. A similar study by Odili et al (2020), it was observed that Aspergillus niger and Monocillium sp. degradaed crude oil better when they were used individually than in consortium.…”
Section: Biodegradation Of Btex By Gliocladium Sp and Aspergillus Tesupporting
confidence: 68%